Per un’etimologia del sistema: itt. ḫe/inkan- (Atti del Sodalizio Glottologico Milanese, 2021)
Towards an etymology of the system: Hitt. ḫe/inkan-. The aim of this paper is to investigate the origin of the Hittite form ḫe/inkan- ‘death, doom, plague’ by focusing on its relationship with the verb hink- ‘bestow’. Although this noun is already attested in the oldest texts, its etymological interpretation is difficult. It will be suggested the semantic development ‘that what has been allotted to someone > ‘bestowal’ > ‘lot, fate’ > ‘fate of death’.
Keywords: ittito; greco omerico; etimologia; cultura indoeuropea; Hittite; Homeric Greek; etymology; Indo-European culture